Manifestations of the boundary in everyday life of a village school - Karapetyan, Nelli (History and Culture, 2025)
In 2020, the Artsakh war and the military-political processes that followed it were accompanied by a number of socio-political, economic, and socio-cultural realities, which led to certain everyday transformations, especially in the settlements that became borderlands. In this report, I sought to observe how this new border situation manifested itself in the daily life of the school operating in the village, using the example of one of the settlements that has became a border after 2020.The academic literature on schooling and education in remote villages typically addresses socio-economic and demographic issues, as well as the importance of the school in ensuring the continuity of the village as a settlement. However, a school is also a socio-cultural phenomenon, encompassing the life space of students and teachers, with its standards of behavior, communication, speech, clothing, physical space characteristics, and the nature of school-community relations. Consequently, the study of the school as a socio-cultural phenomenon is of equal importance. This is particularly relevant in the context of border schools.A socio-cultural study of border schools will enable us to address several fundamental questions. These include whether the reality of the border has been reflected in the school and how it is manifested.
Keywords: border village; border school; everyday life; migration; place of memory